Who's up to the challenge? 34

Calculus Level 5

n = 1 k = 1 ζ ( n + k ) 1 n + k = a γ + b \large \displaystyle\sum _{ n=1 }^{ \infty }{ \displaystyle\sum _{ k=1 }^{ \infty }{ \dfrac { \zeta (n+k)-1 }{ n+k } } } =a\gamma +b

The equation holds true for integers a a and b b , with γ \gamma denote the Euler-Mascheroni constant , γ 0.5772 \gamma \approx 0.5772 .

Find a + b a+b .

Notation : ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 15, 2016

We have (putting N = k + n N = k+n ) n = 1 k = 1 ζ ( k + n ) 1 k + n = N = 2 n = 1 N 1 ζ ( N ) 1 N = N = 2 ( N 1 ) ( ζ ( N ) 1 ) N = N = 2 ( ζ ( N ) 1 ) N = 2 ζ ( N ) 1 N = 1 ( 1 γ ) = γ \begin{array}{rcl} \displaystyle \sum_{n=1}^\infty \sum_{k=1}^\infty \frac{\zeta(k+n)-1}{k+n} & = & \displaystyle \sum_{N=2}^\infty \sum_{n=1}^{N-1} \frac{\zeta(N)-1}{N} \\ & = & \displaystyle \sum_{N=2}^\infty \frac{(N-1)(\zeta(N)-1)}{N} \; = \; \sum_{N=2}^\infty (\zeta(N)-1) - \sum_{N=2}^\infty \frac{\zeta(N)-1}{N} \\ & = & 1 - (1 - \gamma) \; = \; \gamma \end{array} making the answer 1 + 0 = 1 1 + 0 =\boxed{1} . Since all the terms in the series are positive, there is no problem rearranging the series in this manner.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...